Quantitative Analysis of Ra-226, K-40 and Th-232 in Sediment from Rivers and Canals at Surat Thani Province - Kaewtubtim, Pungtip; Phansuke, Piya; Lakkiang, Mubarak; Ruengrung, Sathaphorn (Burapha Science Journal, 2026)
Concentrations of Ra-226, K-40, and Th-232 in 96 sediment samples from rivers and canals at Surat Thani Province were analyzed. The analyses were performed by using a gamma spectrometry with a high purity geranium (HPGe) detector and IAEA-Soil-6 for calibration. The results showed that the average radioactive concentrations of Ra-226, K-40 and Th-232 in sediment from rivers and canals at Surat Thani Province were 42.63 ± 26.08, 125.42 ± 38.58 and 6.29 ± 2.29 Bq/kg, respectively. The concentrations of Ra-226 and Th-232 were higher than the world wide but lower than the Thailand average. In addition, the radium equivalent radioactivity (Raeq) were 61.29 ± 28.75 Bq / kg, the internal hazard index (Hin) were 0.28±0.14, the external hazard index (Hex) were 0.17±0.09, the gamma-absorbed dose rate (D) were 28.69±13.34 nGy/h and the annual external effective dose rate (E) were 0.04 ± 0.01 mSv/ y, respectively. Which is lower than of the United Nations Scientific Committee on the Effect of Atomic Radiation (UNSCEAR, 2000).